2020
DOI: 10.3390/vision4030041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraocular Lens Tilt and Decentration on Visual Acuity, Dysphotopsia and Wavefront Aberrations

Abstract: Tilt and decentration of intraocular lenses (IOL) may occur secondary to a complicated cataract surgery or following an uneventful phacoemulsification. Although up to 2–3° tilt and a 0.2–0.3 mm decentration are common and clinically unnoticed for any design of IOL, larger extent of tilt and decentration has a negative impact on the optical performance and subsequently, the patients’ satisfaction. This negative impact does not affect various types of IOLs equally. In this paper we review the methods of measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 83 publications
6
40
0
Order By: Relevance
“…IOL decentration and tilt were not measured in our study, although both the Liberty and AT LISA tri IOLs have been reported to undergo some decentration following implantation [24,39]. IOL decentration can affect refractive and visual outcomes [38,40]. Kim et al reported a tendency towards myopia among patients implanted with the AT LISA tri 839MP compared to a group implanted with a C-loop haptic IOL [26].…”
Section: Discussionmentioning
confidence: 55%
“…IOL decentration and tilt were not measured in our study, although both the Liberty and AT LISA tri IOLs have been reported to undergo some decentration following implantation [24,39]. IOL decentration can affect refractive and visual outcomes [38,40]. Kim et al reported a tendency towards myopia among patients implanted with the AT LISA tri 839MP compared to a group implanted with a C-loop haptic IOL [26].…”
Section: Discussionmentioning
confidence: 55%
“…In this study, the amount of IOL tilt and decentration of four toric IOLs was approximately 5° and 0.2 mm, respectively, and there were no significant differences among IOLs. The influence of IOL decentration and tilt on visual function varies depending on the design of IOLs [ 15 ]. For toric IOLs, decentration and tilt can result in less predictable correction of astigmatism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pupil size, corneal and total astigmatism, coma, and other ocular aberrations are all reported to have impacts on the postoperative success [2,4,10]. Additionally, MIOLs are widely known to be sensitive to tilt and decentration [11][12][13][14][15][16][17][18]. Tilt and decentration are reported to affect the eye's optical performance and, consequently, decrease optical quality [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%